“Nosotras de robot no tenemos nada”: arreglos intersubjetivos tecnosociales en el trabajo doméstico mediado digitalmente - Laura Clemencia Mantilla-León; Óscar Javier Maldonado Castañeda (Revista de Estudios Sociales, 2024)
This article explores the intersubjective relationships between clients and workers on two digital domestic work platforms in Bogotá, Colombia. Drawing on feminist social studies of science and technology, it investigates the control, auditing, and subordination mechanisms affecting workers, with clients playing a key role in setting performance conditions. While much of the literature on digital labor focuses on technological intermediation and algorithmic management—used to track, monitor, and rate domestic workers—this article looks at the relationships with clients and how these shape the work process and technologies involved. Based on over thirty in-depth interviews with workers and clients, the study examines three areas: (i) clients’ expectations of mechanical efficiency; (ii) the use of rating systems; and (iii) domestic work as emotional labor. The article concludes by reflecting on the dual subordination experienced by workers due to digital service intermediaries and emphasizes the need for fair technologies that consider workers’ experiences and perspectives